Dr. Danielle Salvati — Deep Plane Facelift — Curitiba - Salvati, Danielle (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Danielle Salvati, practicing in Curitiba, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003355; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; curitiba